2020
DOI: 10.3390/ijerph17165908
|View full text |Cite
|
Sign up to set email alerts
|

Improved Documentation of Electronic Cigarette Use in an Electronic Health Record

Abstract: The use of electronic cigarettes (e-cigarettes) can affect patient health and clinical care. However, the current documentation of e-cigarette use in the electronic health records (EHR) is inconsistent. This report outlines how the ambulatory clinical practices of a large U.S. hospital system optimized its electronic health records (EHR) framework to better record e-cigarettes used by patients. The new EHR section for e-cigarette information was implemented for outpatient appointments. During a 30-week evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…10 Compared with these previous investigations, our study analyzed a clinical cohort (ie, patient seeking medical care) and used self -reported e-cigarette use data that were confirmed and documented in an EHR by a clinician. 6 Also, COVID-19 diagnosis in our study was confirmed using a diagnostic PCR test. 7 This analysis is subject to the limitations common to observational cohort studies, for example, inclusion of some, but likely not all, confounding variables (ie, related both to COVID-19 risk and e-cigarette use).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…10 Compared with these previous investigations, our study analyzed a clinical cohort (ie, patient seeking medical care) and used self -reported e-cigarette use data that were confirmed and documented in an EHR by a clinician. 6 Also, COVID-19 diagnosis in our study was confirmed using a diagnostic PCR test. 7 This analysis is subject to the limitations common to observational cohort studies, for example, inclusion of some, but likely not all, confounding variables (ie, related both to COVID-19 risk and e-cigarette use).…”
Section: Discussionsupporting
confidence: 70%
“…Screening utilized a novel electronic health record documentation as previously described. 6 As part of routine clinical care during ambulatory appointments, clinicians ascertain e-cigarette use history from patients and document the information as structured data in the electronic health record (EHR). This documentation framework was implemented in EHR as a quality improvement initiative for our health system since September 2019.…”
Section: Methodsmentioning
confidence: 99%
“…189 190 In part augmented by EMR frameworks that prompt collection of data on vaping history, more recent estimates indicate that a vaping history is being collected in up to 6% of patients. 191 Compared with the widespread use of vaping, particularly among adolescent and young adult populations, this number remains low. Considering generational trends in nicotine use, vaping will likely eventually overcome cigarettes as the most common mode of nicotine use, raising the importance of collecting a vaping related history.…”
Section: Covid-19 and Vapingmentioning
confidence: 99%
“…Retrospective analysis of outpatient visits showed that a vaping history was collected in less than 0.1% of patients in 2015,188 although this number has been increasing 189190. In part augmented by EMR frameworks that prompt collection of data on vaping history, more recent estimates indicate that a vaping history is being collected in up to 6% of patients 191. Compared with the widespread use of vaping, particularly among adolescent and young adult populations, this number remains low.…”
Section: Clinical Impact—collecting and Recording A Vaping Historymentioning
confidence: 99%
“…As of April 2021, 681 (18%) of those referred had completed $1 NDC appointment, of which 173 (27%) were relisted as former smokers in the EHR. C3I support also catalyzed the implementation of changes to infrastructure at the health system level by including structured documentation in the EHR to record e-cigarette use, 14 the establishment of a tobacco and e-cigarette registry, an EHR alert for scheduling staff to update tobacco use history, a patient engagement video delivered via an appointment portal, and use of the NCI's Cancer Patient Tobacco Use Questionnaire. Changing the health system infrastructure as an implementation strategy using an "opt-out" referral workflow that does not require clinician involvement demonstrated effectiveness and sustainability in oncology practices.…”
Section: Cohort 2: Mayo Clinic Cancer Centermentioning
confidence: 99%